Artificial Intelligence and Inclusive Education: Speculative Futures and Emerging Practices - McArdle, Laura (Journal of Interdisciplinary Studies in Education, 2022)
Artificial intelligence and inclusive education: Speculative futures and emerging practices by Knox, Wang, & Gallagher (2019) is a resource for those who both specialize and are novice in artificial intelligence, education, and inclusive education. It provides an accessible sampling of the issues facing technology, ethics, and diversity and inclusion within the education space. Particularly on the heals of the COVID-19 pandemic, scholars and practitioners alike can immerse in the relevant issues regarding technology and AI facing the field today.